2003
DOI: 10.1523/jneurosci.23-17-06884.2003
|View full text |Cite
|
Sign up to set email alerts
|

Response Suppression in V1 Agrees with Psychophysics of Surround Masking

Abstract: When a target stimulus is embedded in a high contrast surround, the target appears reduced in contrast and is harder to detect, and neural responses in visual cortex are suppressed. We used functional magnetic resonance imaging (fMRI) and psychophysics to quantitatively compare these physiological and perceptual effects. Observers performed a contrast discrimination task on a contrast-reversing sinusoidal target grating. The target was either presented in isolation or embedded in a high-contrast surround. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
205
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(232 citation statements)
references
References 87 publications
24
205
3
Order By: Relevance
“…Accordingly, it has been demonstrated that the effect of spatial attention can be significantly increased when one of two stimuli, rather than a single stimulus, is attended (Lavie, 1995;Luck, Chelazzi, Hillyard, & Desimone, 1997). Furthermore, the contrast-decrement detection task of our study is known to strongly modulate attention (Braun, 1994;Zenger-Landolt & Heeger, 2003). The same argument can be made for Moradi et al's study, where participants were simply instructed to attend to a moving suppressor.…”
Section: Resultssupporting
confidence: 74%
“…Accordingly, it has been demonstrated that the effect of spatial attention can be significantly increased when one of two stimuli, rather than a single stimulus, is attended (Lavie, 1995;Luck, Chelazzi, Hillyard, & Desimone, 1997). Furthermore, the contrast-decrement detection task of our study is known to strongly modulate attention (Braun, 1994;Zenger-Landolt & Heeger, 2003). The same argument can be made for Moradi et al's study, where participants were simply instructed to attend to a moving suppressor.…”
Section: Resultssupporting
confidence: 74%
“…Previous block design imaging experiments (Kastner et al, 2004), which have compared contrast response functions measured with ascending versus descending contrasts, may not have been as sensitive to adaptation changes as event-related studies (this study and Engel and Furmanski, 2001). Changes in contrast response functions measured with BOLD imaging have been noted in surround suppression experiments (Zenger-Landolt and Heeger, 2003), sharing some similarities with the effect we find with adaptation. However, surround suppression induces more response-gain changes and is likely to be mediated by neurons with different receptive field locations.…”
Section: Relation To Previous Experimentssupporting
confidence: 86%
“…In fact, our measurements of contrast sensitivity before and after adaptation, indicate that block design experiments (depending on the length of the block) could, in the limit, underestimate contrast sensitivity by more than three times. Accurate measurements of contrast sensitivity are particular important for studies that wish to relate BOLD measurements to behavior Zenger-Landolt and Heeger, 2003) or to level of neural activity (Heeger et al, 2000). Moreover, when comparing contrast sensitivity across areas (Avidan et al, 2002), differences in adaptation rates may result in misestimation of contrast sensitivities.…”
Section: Relation To Previous Experimentsmentioning
confidence: 99%
“…Additionally, the pRF may be modeled using nonlinear models and sums and differences of Gaussians to test hypotheses about surround suppression. These suppressive effects have been demonstrated using fMRI (Dumoulin and Hess, 2006;Kastner et al, 2001;Williams et al, 2003;Zenger-Landolt and Heeger, 2003), and it has been shown that the strength and spatial extent of these suppressive effects increase in later visual areas (Kastner et al, 2001;Zenger-Landolt and Heeger, 2003). This increase may be related to increases in the RF sizes in these areas (Bles et al, 2006;Kastner et al, 2001).…”
Section: Future Extensions and Applicationsmentioning
confidence: 89%